2012
DOI: 10.4049/jimmunol.1102412
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Inhibits Monocyte/Macrophage Proinflammatory Cytokine Production by Targeting MAPK Phosphatase-1

Abstract: It is estimated that one billion people around the world are vitamin D deficient. Vitamin D deficiency has been linked to various inflammatory diseases. However, the mechanism by which vitamin D reduces inflammation remains poorly understood. In this study, we investigated the inhibitory effects of physiologic levels of vitamin D on lipopolysaccharide (LPS)-stimulated inflammatory response in human blood monocytes, and explored potential mechanisms of vitamin D action. We observed that two forms of the vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
541
4
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 731 publications
(598 citation statements)
references
References 48 publications
27
541
4
5
Order By: Relevance
“…Vitamin D deficient people have much higher levels of inflammatory markers than those that get enough vitamin D. Adequate vitamin D decreases this inflammation and has been shown to alleviate lower back pain. Up-regulation of MKP-1 by vitamin D is the novel pathway by which vitamin D inhibits LPSinduced p38 activation and cytokine production in monocytes/macrophages [16]. RANK-RANKL osteoprotegerin system, modulated by vitamin D, directly influences the release of pro inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficient people have much higher levels of inflammatory markers than those that get enough vitamin D. Adequate vitamin D decreases this inflammation and has been shown to alleviate lower back pain. Up-regulation of MKP-1 by vitamin D is the novel pathway by which vitamin D inhibits LPSinduced p38 activation and cytokine production in monocytes/macrophages [16]. RANK-RANKL osteoprotegerin system, modulated by vitamin D, directly influences the release of pro inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that vitamin D increases tight junction proteins and enhances gut mucosal healing post-injury (77) . For example, following exposure to dextran sulphate sodium, a chemical which induces colitis, the VDR knock out mice were unable to maintain the integrity of the epithelial barrier (69,78) and had lower expression of tight junction proteins than in wild-type mice (77)(78)(79) . As a result of reduced tight junction proteins, vitamin D-deficient and VDR knock out mice had increased gut permeability compared with vitamin D-sufficient wild-type mice (78) .…”
Section: Vitamin D and Immune Function In Crohn's Disease: Experimentmentioning
confidence: 99%
“…The presence of VDRs in human T lymphocytes [Provvedini et al 1983;Baeke et al 2010], in greater number in CD8 than in CD4 lymphocytes [Vedman et al 2000], as well as in B lymphocytes [Provvedini et al 1983;Chen et al 2007], and the expression of CYP27B1 in lymph nodes [Zehdner et al 2001] and T lymphocytes [Sigmundsdottir et al 2007] constitute important indications of a potential role of vitamin D in adaptive immunity. Furthermore, a number of mechanisms by which vitamin D and calcitriol could favourably influence immunity have been reported in the past 30 years: it has been shown that vitamin D (through calcitriol) reduces differentiation of monocytes to DCs and differentiation and proliferation of DCs, thus decreasing T-cell stimulation [Griffin et al 2001]; controls T-cell activation [von Essen et al 2010] and inhibits T-cell proliferation [Rigby et al 1990;Lemire et al 1984]; reduces the production of interleukin (IL)-2 (growth factor for T cells) [Müller et al 1993]; suppresses in vitro and in vivo production of proinflammatory Th1 cell-derived IFNγ and tumour necrosis factor α [Reichel et al 1987;Lemire et al 1995;Baeke et al 2010;Zhang et al 2012]; reduces proinflammatory Th17 activity and IL-17 production [Tang et al 2009;Ikeda et al 2010;Bruce et al 2011;Joshi et al 2011;Allen et al 2012]; enhances the production of the antiinflammatory cytokine IL-10 [ Heine et al 2008;Baeke et al 2010;Allen et al 2012]; promotes in vitro and in vivo the development of Tregs expressing cytotoxic T lymphocyte antigen 4 and forkhead box P3, resulting in an anti-inflammatory effect [Jeffery et al 2009;Prietl et al 2010;Khoo et al 2012;Urry et al 2012]; enhances the transformation of CD4 T lymphocytes into a Th2 phenotype (with a protective role) [Boonstra et al 2001;…”
Section: General Immunodulatory Effect Of Vitamin D In Humansmentioning
confidence: 99%